Later one knows better: the over-reporting of short-time work in firm surveys - Christian Kagerl; Malte Schierholz; Bernd Fitzenberger (Journal for Labour Market Research, 2022)
Short-time work (STW) in Germany allows for a lot of flexibility in actual usage. Ex ante, firms notify the Employment Agency about the total number of employees eligible, and, up to the total granted, firms can flexibly choose how many employees actually use STW. In firm-level surveys, which provide timely information on STW in Germany, over-reporting of the number of employees on STW is prevalent. This study explores reasons for STW over-reporting based on a high-frequency and low-cost survey initiated during the Covid-19-pandemic (BeCovid) and a low-frequency and high-cost long-running survey (BP). Merging administrative records on actual use of STW, firms that use STW prove more likely to participate in the BeCovid survey. Multi-establishment firms over-report STW because they tend to report STW for all subfirms. The BP uses more interview time and confirms the over-reporting of STW use in the survey month, while - crucially - the over-reporting drops sharply with a few months of retrospection.
Keywords: C83; J63; J65; 330; Establishment surveys; Measurement error; Non-response bias; Short-time work; Survey evidence